Integrating Sharia Principles in Infrastructure Finance: A Government-Business Partnership Scheme for Sustainable Development - Nasrulloh; Widodo, Sugeng; Nur Efendi, Mohamad; Septiana, Nurul Izzati (Journal of Islamic Economic and Business Research, 2025)
This research explores the financing of infrastructure through the Public-Private Partnership (PPP) scheme, referred to as Kerjasama Pemerintah dan Badan Usaha (KPBU) in Indonesia, and Sharia finance. With the increased global need for sustainable infrastructure, the PPP scheme presents an opportunity to accelerate development in a Sharia-compliant way. This compliance includes the forbidding of lending with interest (riba), uncertainty (gharar), and gamble-like activities (maisir). This study employs a literature review methodology focusing on publications dated 2018 and 2024 and synthesizes existing literature on the Sharia-based PPP models. Significant findings indicate that the PPP schemes combined with the Istisna modality make it possible to comply with the basic Sharia legal requirements, enabling progressive payments to be made in accordance with project milestones. A repayment structure that is paid in stages rids people of the burden of usury and enhances transparency while reducing financial risks. Insight from primary data reveals that through effective regulation and stakeholder participation, along with adequate supervision, transparency and efficiency can be greatly enhanced. The added contribution of this research is that it develops a practical operational framework for the Sharia PPPs, which can be utilized in almost all infrastructure developmental activities. These frameworks propose measurable efficiency and accountability while complying with Islamic financial requirements. The findings present sharia infrastructure financing that is equitable, effective, and sustainable, providing fundamental policy insights to regulators, sharia practitioners, and other stakeholders.